Pengaruh Harga, Inovasi Produk dan Promosi Terhadap Keputusan Pembelian Minyak Kayu Putih Asli Klitikan - Firda Tama; M. Fathur Rahman (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study was conducted in Klitikan Village, Kedungjati Subdistrict, Grobogan Regency to analyze the partial effects of price, product innovation, and promotion on the purchase decision of authentic Klitikan eucalyptus oil. The method used was a quantitative approach with a causal design, involving 100 respondents selected through nonprobability sampling techniques. Data were collected using a 1–5 Likert scale questionnaire and analyzed using SEM-PLS with the assistance of SmartPLS version 4. The test results indicate that price (coefficient 0.249; P-Value 0.000), product innovation (coefficient 0.440; P-Value 0.000), and promotion (coefficient 0.320; P-Value 0.000) each have a positive and significant effect on purchasing decisions. These findings indicate that businesses need to set prices that are in line with purchasing power, engage in continuous innovation, and optimize digital promotions to increase consumer interest in purchasing.